BEHAVIOR OF HIGH STRENGTH REINFORCING STEEL BARS IN EARTHQUAKE-RESISTANT STRUCTURE ELEMENTS WITH CYCLIC LOADING - SETIADI KAMARUDDIN - NIM: 25015309, KURNIAWAN
Currently, design of reinforced concrete building is still dominated with normal strength reinforcing bars, not exceeding 420 MPa of yield strength. Meanwhile, the use of higher strength reinforcing bars tend to increase due to some benefits in the construction, such as reducing the total weight of reinforcing bars and alleviating reinforcing bars congestions. In this study, reinforcing bars with yield strength of 520 MPa are utilized in the reinforced concrete beam-column joint. The objective is to study the the seismic performance of reinforced concrete beam-column joint. A total of 3 interior beam-column joints, half-scaled specimens with different yield strength and bar diameter was tested. One of the test specimens with 16 mm diameter of normal strength reinforcing bars is used as a control specimen. The other two specimens use high strength reinforcing bars, having 16 mm and 19 mm bar diameter. Loading protocol of all the specimens is conformed with ACI 374.2. Dissipation energy and stiffness degradation of the joints is then compared. Normalized energy dissipation of the specimens with high strength reinforcing bars slightly lower than that of the specimens with normal reinforcing bars. However, at the end of the loading, the specimens with high strength reinforcing bars tends to have slightly smaller stiffness degradation than that of the specimens with normal reinforcing bars.